(untitled) (Mustansiria Dental Journal, 2018)
Background: Awareness of the epidemiological characteristics of oral cancers allow for enhanced planning of timely and effective treatment in order to improve patients’ life quality. Despite the fact that oral and perioral cancers are not included in common cancers, they are of special importance for their impact on human morbidity and life quality. Aim of the present study was to investigate the distributional patterns of oral and perioral malignancies in terms of age, gender, type and location. Materials and Methods: 4179 Oral and Maxillofacial cases taken over 5 years (2009 - 2013) at the Department of Oral and Maxillofacial Surgery, Specialist Surgeries Hospital, Medical city, Baghdad, were studied. Among these, 707 biopsy specimens were made for histopathological diagnosis, 182 cases included oral malignant lesions and the rest cases were benign lesions. The data involve age, gender, location, and type of malignancy for these cases were recorded. Results: The results of this survey showed that the most common malignant oral lesions were of epithelial origin with 121 cases (66%), salivary lesions with 20 cases (11%), and hematogenic malignancies with 18 cases (10%). Squamous cell carcinoma, adenoid cystic carcinoma and lymphoma were the most common malignant lesions in this area of the body. The mean age of patients was (39.1) years of old and the male to female ratio was found to be 1.3:1. Conclusion: In this study, epithelial malignant tumors constituted the majority of diagnosed malignant tumors followed by salivary malignant tumors and lymphomas.